PENILAIAN TERHADAP TINGKAT KEMATANGAN DALAM PENINGKATAN EFISIENSI BIAYA IT DAN KONTRIBUSINYA PADA KEUNTUNGAN BISNIS (STUDI KASUS: HOTEL TICKLE YOGYAKARTA) - Selviana Yunita (Informasi Interaktif, 2020)
Hotel is one of the main aspect to provide the tourism and business. The use of Information system is in all aspect of life, including in hospitality business, so Hotel use Information system to support their business process. Tickle Hotel is one of two star hotelthat implements information system to make the business proses easier. The use of Information System certainly need some funds to make sure the information system suitable for hotel’s business process. The funds is one of the form of investment from Hotel to gain optimal profit in the existence of information system. Based on this preposition, the author is interested in conducting research to find out whether the investment that has been issued by the hotel has provided optimal results to support its business activities.This research use COBIT 4.1 as the framework which focus on business goals that is financial perspective, how the IT investment give the good result to the company with PO1 domain for manage the IT Investment and DS6 domain for identify and allocate costs. The research was conducted using a questionnaire distributed to hotel employees, and then be obtained the value of the level of maturity of each domain. Based on the results of the research, the average value obtained for the PO1 domain was 2.64 and DS6 was 2.63.  Keywords: Hotel, Information System Audit, Finance Perspective, Balanced Scorecard, COBIT 4.1.